Partially dead, partially separated: establishing the mechanism between ambiguous loss and grief reaction among caregivers of patients with prolonged disorders of consciousness. (February 2019) - Zaksh, Yael; Yehene, Einat; Elyashiv, Maya; Altman, Arie
Objectives: To trace the psychological mechanism underlying caregivers' emotional experience in prolonged disorders of consciousness, by examining the mediating role of boundary ambiguity in the relationship between ambiguous loss and grief. Design: Cross-sectional design. Setting: The Respiratory Rehabilitation Division of a long-term medical and rehabilitation institute. Subjects: A total of 64 primary caregivers (69% female) of patients in a vegetative state ( n  = 49) or minimally conscious state ( n  = 15), with a mean age of 55.5 (SD = 12.3) years. Participants were mostly the patient's children (62%) or partners (27%). The mean caregiving duration was 4.9 (SD = 5.1) years. Main measures: The Boundary Ambiguity Scale, the Revised Need for Closure Scale, an adapted version of the multifactor Two-Track Bereavement Questionnaire, and a sociodemographic questionnaire, which included items regarding caregiving: frequency of visits and perception of the patient's psychological presence. Results: (1) Caregivers' grief scores (total TTBQ: mean = 2.97; SD = 0.55) did not significantly differ from those exhibited by a normative bereavement sample. (2) Time since injury did not affect caregivers' grief scores (three-year cut-point; P  > .05). (3) Mediation analyses revealed that boundary ambiguity (mean = 34.03; SD = 7.55) significantly mediates the relationship between need for closure ( B  = .11; confidence interval (CI) = .04–.23) and grief; frequency of visits ( B  = .05, CI = .02–.10) and grief and perception of psychological presence ( B  = .26, CI = .00–.61) and grief in three separate models. Conclusion: Ambiguity concerning relational boundaries hinders caregivers' ongoing grief reaction and impedes their ability to integrate the loss. High frequency of visits, belief in the patient's psychological presence and difficulties in tolerating uncertainty are all clinical manifestations of caregivers' entangled experience.